A Simple and Efficient Mechanism to Detect and Avoid Wormhole Attacks in IP network through LOLS - Divekar, Anuja Sanjay; Borade, Deepali; Bugad, Vivek (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
It has been observed that IP networks are vulnerable to many kinds of attacks. Among the various attacks possible in IP networks wormhole attack is one which is treated as a very severe attack. In LOLS, multiple failures are handled but network attack is not detected. LOLS cannot handle any kind of attack and this is the reason why we are working on wormhole attack and its detection by using AOMDV algorithm. In this attack a harmful node records packets at one end in the network and tunnels them to another harmful node which is present in the other end of the network. In this paper, we have proposed an algorithm which detects andÂ  avoids the wormhole attack while data transfer . In this paper one mechanism is used, which is based on the total round trip time (RTT) of current route and the average round trip times This mechanism works for both mobile ad hoc networks and wireless ad hoc networks.